Service Quality and Brand Image Influence Customer Satisfaction and Its Impact on Customer Loyalty CV. Asritama Lestari Environmental Consulting and Licensing Services - Agustin Lestari, Asri; Rachmawati, Mariana (DINASTI RESEARCH, 2025)
This study aims to analyze the influence of service quality and brand image on customer satisfaction and its impact on customer loyalty at CV. Asritama Lestari Environmental Consultant Services and Licensing. . This study examines the associative relationship between these variables. The results of the study show that all variables consisting of service quality, brand image, customer satisfaction, and customer loyalty have a significance level of <5%, which means that simultaneously there is a significant influence between service quality variables and brand image variables on customer loyalty with customer satisfaction as an intervening variable. Partially, the results of the analysis show that service quality and brand image have a positive and significant effect on customer satisfaction. In addition, the results of the analysis also show that service quality and brand image have a significant effect on customer loyalty. Furthermore, customer satisfaction is proven to have a significant and strengthening influence on customer loyalty.